2010
DOI: 10.1089/scd.2009.0351
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Programmable Cells of Monocytic Origin Involves Partial Repression of Monocyte/Macrophage Markers and Reactivation of Pluripotency Genes

Abstract: We have recently demonstrated that peripheral blood monocytes can be differentiated in vitro into hepatocyte-like cells using appropriate differentiation media. Phenotype conversion required prior in vitro culture in the presence of M-CSF, IL-3, and human serum, during which the cells acquired a state of plasticity, so were termed "programmable cells of monocytic origin" (PCMO). Here, we have further characterized the process of PCMO generation with respect to markers of monocyte-to-macrophage transition and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 47 publications
0
39
1
Order By: Relevance
“…p47 phox an essential subunit of the reactive oxygen producing enzyme NAD(P)H oxidase and upregulate markers of pluripotency, e.g. Nanog [6]. We have examined the effect of EGF and HB-EGF on the expression of p47 phox by immunoblotting (Figure 3A) and on the expression of Nanog by qPCR (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p47 phox an essential subunit of the reactive oxygen producing enzyme NAD(P)H oxidase and upregulate markers of pluripotency, e.g. Nanog [6]. We have examined the effect of EGF and HB-EGF on the expression of p47 phox by immunoblotting (Figure 3A) and on the expression of Nanog by qPCR (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, a modification of the PCMO generation procedure, e.g. by addition of growth-stimulatory factor(s), should not only enhance mitotic activity but also the plasticity of PCMOs in such a way that the resulting NeoHepatocytes become more hepatocyte-like [6]. Interestingly, a subpopulation of human monocytes that proliferates in vitro in response to M-CSF has been suspected to be less mature and hence more stem cell-like than other monocytes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ungefroren et al confirmed a change of the monocytes phenotype towards a more stem-cell-like appearance during a 6-day dedifferentiation treatment. The cells downregulated some monocyte-defining gens and started to express stem cell markers over time [19]. Recently, our group demonstrated that dedifferentiation of monocytes towards PCMOs with subsequent hepatogenic differentiation can be significantly improved by the use of the patient's autologous serum instead of human AB serum or fetal calf serum (FCS) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes have also been used by our group (12) and by Hur et al (13) to generate insulin-producing cells. Our protocol includes growth factors treatment for subsequently undergoing dedifferentiation followed by programmability (12).…”
Section: Introductionmentioning
confidence: 99%
“…Our protocol includes growth factors treatment for subsequently undergoing dedifferentiation followed by programmability (12). We have previously shown that these programmable cells of monocytic origin (PCMO) can then differentiate into insulin-producing cells (14) and hepatocyte-like cells (neo-hepatocytes) (15).…”
Section: Introductionmentioning
confidence: 99%